2023
DOI: 10.1136/bmjebm-2022-112079
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reviews methods series: Guidance on literature search

Abstract: This paper is part of a series of methodological guidance from the Cochrane Rapid Reviews Methods Group. Rapid reviews (RR) use modified systematic review methods to accelerate the review process while maintaining systematic, transparent and reproducible methods. In this paper, we address considerations for RR searches. We cover the main areas relevant to the search process: preparation and planning, information sources and search methods, search strategy development, quality assurance, reporting, and record m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…It may be most appropriate in the context of rapid reviews, where there is a need to complete a review in a short timeframe with limited resources to screen studies. In such reviews, search strategies that maximise precision over sensitivity may be selected 23,23 . However, using such a strategy risks missing a large percentage of eligible ITS studies, which should be reported as a limitation of the review.…”
Section: Discussionmentioning
confidence: 99%
“…It may be most appropriate in the context of rapid reviews, where there is a need to complete a review in a short timeframe with limited resources to screen studies. In such reviews, search strategies that maximise precision over sensitivity may be selected 23,23 . However, using such a strategy risks missing a large percentage of eligible ITS studies, which should be reported as a limitation of the review.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a swift study 19 to identify all the documented cases of fungal infections resulting from CARD9 deficiency. The case reports were selected using PubMed, Embase, Scopus and Google Scholar database between October 2009 and November 2022.…”
Section: Methodsmentioning
confidence: 99%
“…The development of the literature search and screening strategy ( Klerings et al, 2023 ), along with data extraction, was initially designed by the first two authors. A review meeting involving all four authors was conducted to assess the research design strategy.…”
Section: Methodsmentioning
confidence: 99%